2022
DOI: 10.1038/s41598-022-05842-3
|View full text |Cite
|
Sign up to set email alerts
|

The potential of invasive and non-invasive vagus nerve stimulation to improve verbal memory performance in epilepsy patients

Abstract: It has been demonstrated that acute vagus nerve stimulation (VNS) improves word recognition memory in epilepsy patients. Transcutaneous auricular vagus nerve stimulation (taVNS) has gained interest as a non-invasive alternative to improve cognition. In this prospective randomized cross-over study, we investigated the effect of both invasive VNS and taVNS on verbal memory performance in 15 patients with drug-resistant epilepsy. All patients conducted a word recognition memory paradigm in 3 conditions: VNS ON, V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…62 Because no study to date has examined the effects of TAVNS on PSCI prevention or treatment, our design is based on assessments of verbal memory performance in patients with epilepsy. Mertens et al 29 reported improved verbal memory performance after 6 weeks of VNS. Considering that our TAVNS intervention will begin around week 4 poststroke, and that 12 weeks is widely recommended as the diagnostic time point for PSCI, it is reasonable to extend treatment to 8 weeks so that we can examine cognitive function changes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…62 Because no study to date has examined the effects of TAVNS on PSCI prevention or treatment, our design is based on assessments of verbal memory performance in patients with epilepsy. Mertens et al 29 reported improved verbal memory performance after 6 weeks of VNS. Considering that our TAVNS intervention will begin around week 4 poststroke, and that 12 weeks is widely recommended as the diagnostic time point for PSCI, it is reasonable to extend treatment to 8 weeks so that we can examine cognitive function changes.…”
Section: Discussionmentioning
confidence: 98%
“… 26 Functional brain imaging has shown that TAVNS and iVNS have similar activation patterns, suggesting that the former effectively activates vagal trajectories and has the potential to induce similar effects. 27 28 Clinical studies have also shown that TAVNS can effectively improve cognitive function in those with epilepsy 29 and depression, 30 and in healthy individuals. 31 32 However, whether TAVNS has the same effects in those with PSCI is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of effect of tVNS on social behavior in healthy participants and the associated neural networks will be subject to future studies. Nevertheless, recent studies indicate that discrepancies between the outcome of studies investigating VNS effects on cognition in epilepsy patients and healthy participants, e.g., on recognition memory 14 , 59 , are a result of different modes of VNS application, i.e., invasive vs. transcutaneous stimulation respectively, rather than the pathology 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This goes in line with evidence from human imaging studies indicating that tVNS is associated with blood-oxygen-level-dependent (BOLD) changes in brain areas involved in reward-processing, such as the dopaminergic midbrain and striatum 12 , 13 . Based on current evidence, these effects are function-specific, as studies failed to observe general effects, i.e., effects across age groups, the study population and independent of emotional processing, of tVNS on other cognitive functions such as recognition memory 14 , 15 , implicit learning 16 , conflict processing 17 , 18 or response inhibition 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous vagus nerve stimulation is shown to enhance the associative memory in older individuals ( Jacobs et al, 2015 ). A recent study found that 6 weeks of VNS treatment triggered improvement in immediate recall and delayed recognition scores examined in epileptic patients ( Mertens et al, 2022 ). The authors concluded that longer and more repetitive stimulation of the vagus nerve may be required to effectively modulate memory performance.…”
Section: Vagus Nerve Stimulation Strategymentioning
confidence: 99%